Perceptual Model Relating Ambient Light Condition and Perception of Privacy: A Stimuli Perception Experiment (A Dissertation Proposal) - Pornchai Tamthinthai; Nopadon Sahachaisaeree (My University, 2010)
Abstract The Gestalt principle of perceptual organization argues that environment users perceive the overall configuration of the space rather than perceiving its elements separately. Perception of functionality in a particular interior space is influenced by the environmental appearance in accordance with the person's past experiences. This research attempts to associate the ambient lighting condition with the perceived functionality of the built environment, hypothesizing that the process works through the mood factor. In this initial research tool testing state, the research utilizes a set of 3D visual stimuli together with a questionnaire self-report to solicit response from subjects and a semantic differential method to analyze the data.
Keywords: Urban Green Space and Health